Effect of collection-maturation interval time and pregnancy status of donor mares on oocyte developmental competence in horse cloning - Gambini, Andres (2013)
The current limitations for obtaining ovaries from slaughterhouses and the low efficiency of in vivo follicular aspiration necessitate a complete understanding of the variables that affect oocyte developmental competence in the equine. For this reason, we assessed the effect on equine oocyte meiotic competence and the subsequent in vitro cloned embryo development of 1) the time interval between ovary collection and the onset of oocyte in vitro maturation (collection-maturation interval time) and 2) the pregnancy status of the donor mares. To define the collection-maturation interval time, collected oocytes were classified according to the slaughtering time and the pregnancy status of the mare. Maturation rate was recorded and some matured oocytes of each group were used to reconstruct zona free cloned embryos. Nuclear maturation rates were lower when the collection-maturation interval time exceeded 10 h as compared to 4 h (32/83 vs. 76/136, respectively; P = 0.0128) and when the donor mare was pregnant as compared to nonpregnant (53/146 vs. 177/329, respectively; P = 0.0004). Low rates of cleaved embryos were observed when the collection-maturation interval time exceeded 10 h as compared to 6 to 10 h (11/27 vs. 33/44, respectively; P = 0.0056), but the pregnancy status of donor mares did not affect cloned equine blastocyst development (3/49 vs. 1/27 for blastocyst rates of nonpregnant and pregnant groups, respectively; P = 1.00). These results indicate that, to apply assisted reproductive technologies in horses, oocytes should be harvested within approximately 10 h after ovary collection. Also, even though ovaries from pregnant mares are a potential source of oocytes, they should be processed at the end of the collection routine due to the lower collection and maturation rate in this group.